Protagonismo infantil na escola do campo: caminhos para a (re)organização das práticas pedagógicas e do espaço/tempo escolares - Melo, Keylla Rejane Almeida (2019)
Based on assumptions of the Sociology of Childhood and Rural Education, this study deals with child protagonism of peasant children in the school context. The conception of children as a social subject refers to the consideration of their experiences and points of view in the (re)organization of this context. The research in question presents as a problem: How can the educational spaces / times of rural schools be (re) organized from the senses produced by the peasant children about the countryside and the rural school? The general objective of the research was: To understand the (re) organization of the educational spaces / times of rural schools based on the senses produced by the peasant children about the countryside and the rural school. Specifically, it aimed to: Characterize the configuration of the Brazilian and Piauiense countryside, highlighting the communities of the research scenarios; To identify the meanings that the peasant children produce on the ways of life in the countryside and on the rural school; To analyze the repercussions of these senses in the forms of (re) organization of the educational space / time of rural schools that work in peasant childhood education. Its methodological orientation is included in the Narrative Survey, with a qualitative approach. The data were produced, mainly, from the realization of focus groups, having as devices for the triggering of the interactions photographs and drawings made by the co-participants of the study. Anchored in Gatti (2005), the procedures of data analysis start from the construction of a descriptive plan of the speeches, highlighting the differences between the reports and grouping them according to the perceived senses, which later enabled the categorization of these speaking, always emphasizing the interaction between the narratives. The research scenarios were, more broadly, two rural communities of two municipalities in the center of northern Piauí and, more specifically, the two schools located in these communities. The co-participants of the study were 20 (twenty) children aged 8 to 10 years who study at these rural schools. The results of the study showed that children have the potential to participate actively in decision-making bodies in the social sphere, especially the school, as an institution that covers a considerable amount of their daily living. This institutional insertion enables them, from lived experiences, to give meaning to the school and its pedagogical practices. Therefore, as beings of experiences, children act and their actions modify institutional and social structures, and it is urgent that they be recognized as social actors, and that this status serves as a motto for (re) organization of spaces, times and knowledge in the surveyed schools so that the protagonism of children is gradually developed through more democratic pedagogical practices.